EMPLOYEE COMPENSATION EVALUATION BASED ON COST OF LIVING ADJUSTMENT (COLA) IN RETAIL INDUSTRY BOGOR, INDONESIA - Aldy Rizaldy; Lindawati Kartika; Roni Jayawinangun (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The retail industry is a field that has a high contribution to the Indonesian economy. This research will examine the compensation based on the need for a decent living for retail workers. The purpose of this study is to (1) Analyze and evaluate the fulfillment of compensation (2) Creating a design and compensation strategy based on the requirements of decent living in Bogor. The type of data in this study is primary data (interview and questionnaires) and secondary data obtained from the website of Bogor, BPS, literature study, and relevant report. The method used is the descriptive analysis, control chart, and Grid ERRC. The results show that according to 60 components of Living Standards/KHL, only 53 items have been fulfilled and the rest (7 items are expected to be reviewed/Omited) and equal to Rp 2.753.000 which are below to Minimum Wage in Bogor. There is a priority in financial compensation and non-financial compensation, which are health benefits, holiday benefits, work accidents, and work incentives and non-financial compensation consists of career systems, work facilities, responsibilities, work status, working conditions. According to the control chart only 38% of the total respondents whose number of the COLA can be fulfilled above the average retail sector worker.